Numerical simulations for radon migration and exhalation behavior during measuring radon exhalation rate with closed-loop method - Xia, Ming; Ye, Yong-Jun; Liu, Shu-Yuan (Nuclear science and techniques, 2024)
Accurate measurements of the radon exhalation rate help identify and evaluate radon risk regions in the environment. Among these measurement methods, the closed-loop method is frequently used. However, traditional experiments are insufficient or cannot analyze the radon migration and exhalation patterns at the gas–solid interface in the accumulation chamber. The CFD-based technique was applied to predict the radon concentration distribution in a limited space, allowing radon accumulation and exhalation inside the chamber intuitively and visually. In this study, three radon exhalation rates were defined, and two structural ventilation tubes were designed for the chamber. The consistency of the simulated results with the variation in the radon exhalation rate in a previous experiment or analytical solution was verified. The effects of the vent tube structure and flow rate on the radon uniformity in the chamber; permeability, insertion depth, and flow rate on the radon exhalation rate and the effective diffusion coefficient on back-diffusion were investigated. Based on the results, increasing the insertion depth from 1 to 5 cm decreased the effective decay constant by 19.55%, whereas the curve-fitted radon exhalation rate decreased (lower than the initial value) as the deviation from the initial value increased by approximately 7%. Increasing the effective diffusion coefficient from 2.77 × 10 −7 to 7.77 × 10 −6 m 2 s −1 made the deviation expand from 2.14 to 15.96%. The conclusion is that an increased insertion depth helps reduce leakage in the chamber, subject to notable back-diffusion, and that the closed-loop method is reasonably used for porous media with a low effective diffusion coefficient in view of the back-diffusion effect. The CFD-based simulation is expected to provide guidance for the optimization of the radon exhalation rate measurement method and, thus, the accurate measurement of the radon exhalation rate.